2009
DOI: 10.1590/s0100-06832009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Marcha de absorção do nitrogênio do solo, do fertilizante e da fixação simbiótica em feijão-caupi (Vigna unguiculata (L.) walp.) e feijão-comum (Phaseolus vulgaris L.) determinada com uso de 15N

Abstract: RESUMO(1) Recebido para publicação em dezembro de 2007 e aprovado em maio de 2009.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 25 publications
1
13
1
8
Order By: Relevance
“…According to Brito et al (2009), the largest proportion of N absorbed by common bean (around 80 %) was derived by symbiotic fixation, and the highest rate of N symbiotic fixation occurred at the pre-flowering stage. Haag et al (1967) found that Mg was absorbed up to 70 DAE, i.e., a similar period as observed in this study (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…According to Brito et al (2009), the largest proportion of N absorbed by common bean (around 80 %) was derived by symbiotic fixation, and the highest rate of N symbiotic fixation occurred at the pre-flowering stage. Haag et al (1967) found that Mg was absorbed up to 70 DAE, i.e., a similar period as observed in this study (Figure 6d).…”
Section: Resultsmentioning
confidence: 99%
“…The BNF is able to provide the necessary N for cowpea, following of a descending order by the soil and fertilizers (Brito et al, 2009). Oliveira (2003), cultivated cowpea (cv.…”
Section: Grain Yieldmentioning
confidence: 99%
“…Additionally, the low recovery of the N in the fertilizers -around 50-60 % (Cantarella, 2007) -highlights the need to seek alternatives that enable the use of local inputs without affecting agricultural production (Perez et al, 2004). Thus, the use of legumes that can efficiently facilitate BNF may contribute to the economic viability and sustainability of coffee production systems by reducing the need for use of synthetic N (Brito et al, 2009;Guimarães et al, 2016).…”
Section: Introductionmentioning
confidence: 99%